Performance comparison of intraosseous devices and setups for infusion of whole blood in a cadaveric swine bone model - Lee, Katherine J.; McGuire, Morgan M.; Harvey, Warren C.; Bianchi, William D.; Emerling, Alec D.; Reilly, Erin R.; Bebarta, Vikhyat S.; Lopez, Jason J.; Zarow, Gregory J.; Auten, Jonathan D. (The American journal of emergency medicine, 2022)
Intraosseous (IO) access can provide a critical bridge for blood product infusion when peripheral venous access is not obtainable. Successful pressurized IO infusion requires flow rates sufficient to preserve life, but with infusion pressures low enough to avoid clinical complications (e.g., hemolysis, bone damage, fat emboli). However, the optimal method for pressured IO delivery of blood was unknown. Three trained physicians infused 500 mL of whole blood through a 15-gauge, 45 mm IO catheter into fresh, high bone density cadaveric swine proximal humeri. Participants applied eight different pressure infusion strategies: (1) gravity, (2) pressure bag, (3) pressure bag actively maintained at or above 300 mmHg, (4) hand pump, (5) hand pump with pressure bag, (6) push-pull with 10 mL syringe, (7) push-pull with 60 mL syringe, and a (8) Manual Rapid Infuser in a randomized within-subjects design (30 trials per method, 240 trials total). The primary outcomes of flow rates, mean and peak pressures, and user ratings were contrasted using ANOVA at p < 0.05. The Manual Rapid Infuser conferred the highest flow rates (199 ± 3 mL/min) and most favorable user ratings, but also the highest mean and peak pressures. Push-pull conferred the next highest flow rates (67 ± 5 mL/min for 60 mL, 56 ± 2 mL/min for 10 mL) and pressures, with intermediate-to-high user ratings. Hand pump flow rates were essentially identical with (45 ± 4 mL/min) or without (44 ± 3 mL/min) pressure bag, with high user ratings without a pressure bag. Pressure bag and gravity methods conferred low flow rates and user ratings. Some pressured IO infusion methods can achieve flow rates adequate to serve as a resuscitative bridge in the massively hemorrhaged trauma victim, but flow rates and pressures vary greatly across IO pressurized infusion methods. Manual Rapid Infuser and push-pull methods conferred high flow rates but also relatively high pressures, highlighting the importance of using in vivo models in future research to assess the possible clinical complications of using these promising methods. Combined, present findings highlight the importance of studying pressurized IO methods towards preserving the life of the critically injured trauma victim.